2010
DOI: 10.1111/j.1365-3024.2010.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Naegleria fowleri infection in mice immunized with Cry1Ac plus amoebic lysates is dependent on the STAT6 Th2 response

Abstract: We previously reported that intranasal administration of Cry1Ac protoxin alone or in combination with amoebic lysates increases protection against Naegleria fowleri meningoencephalitis in mice. Those results suggested that both antibody responses and innate immune mechanisms may be participating in the protective effects observed. The present study was aimed to investigate whether the STAT6-induced Th2 immune response is essential for the resistance to N. fowleri infection, conferred by immunization with amoeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…In a previous study, we observed that immunization with N. fowleri plus CT and Cry1Ac as adjuvants display a functional Th2 profile with an increment in the secretion of IgA and IgG antibodies . These findings are reflected in the present study where we found that immunization with all treatments generated IgA antibody‐secreting cells, and this induction was higher in NALT and NP than CN and SP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a previous study, we observed that immunization with N. fowleri plus CT and Cry1Ac as adjuvants display a functional Th2 profile with an increment in the secretion of IgA and IgG antibodies . These findings are reflected in the present study where we found that immunization with all treatments generated IgA antibody‐secreting cells, and this induction was higher in NALT and NP than CN and SP.…”
Section: Discussionsupporting
confidence: 85%
“…Intranasal immunization (i.n) with amoebic lysates plus cholera toxin (CT) as adjuvant increased up to 100% survival in challenged mice with lethal dose of the amoeba . In a previous study, we have proposed that a STAT6‐dependent immune response (Th 2 response) is crucial to induce vaccine protection against N. fowleri meningoencephalitis . Furthermore, this immunization scheme induces an increase in areas with metaplasia in the olfactory epithelium, allowing the secretion of IgA and IgG antibodies .…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators suggest that Bt -maize may have an adjuvant effect that requires testing [17][20], [26][30]. In 2009, EFSA reported that consumption of Bt -maize by humans and animals is safe [14].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Cry1Ac delivered intranasally generated an antibody response, stimulated nasal-associated lymphoid tissue lymphocytes to produce Th2 cytokines, and induced a proportion of T cells to spontaneously produce IL-4, IL-5, and IL-10 [27]. Indeed several studies have shown that Cry1Ac has adjuvant effects using non-physiological approaches [28][30] and it is not clear from these reports whether Cry1Ac effects also apply to Cry1Ab .…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested Th2‐biased immune response which was correlated with the presence of STAT6 protein. Further, high production of IgG1 and IL‐4 took place in the STAT6+/+ mice while the STAT6−/− mice showed IL‐12, IFN‐γ and Th1‐associated IgG2a production …”
Section: Managementmentioning
confidence: 98%